Decision Support System For Example Employee Selection Ministry Of Religion Of Deli Serdang Regency With Analytic Hierarchy Process Method - jonathan laia; Farida Gultom (Jurnal ICT : Information and Communication Technologies, 2021)
The absence of selection of exemplary employees at the Ministry of Religion of Deli Serdang Regency has caused the performance and performance of employees to decline Decision support systems are interactive information systems that provide information, model and manipulate data. The decision support system for selecting exemplary employees is not used as a substitute for decisions, but as a support for decision making. The criteria set by the company in applying for credit are discipline, work performance, commitment, responsibility and quality of performance. With the AHP method, from the criteria determined the intensity of importance/priority scale on the criteria. After performing the calculation process, the decision to select exemplary employees was obtained from the ranking of the AHP method: 0.2669947 (rank 1), 0.25695721 (rank 2), 0.2446883 (rank 3), 0.229045 (rank 4). Keywords: motorcycle loan, SPK, AHP method